Vom selbst-verständnis in antike und neuzeit = Notions of the self in antiquity and beyond - Arweiler, Alexander; Möller, Melanie (Transformationen der Antike, 2008)
The interdisciplinary debate about the genesis of the autonomous subject has tended hitherto to ignore the pre-modern period. The present collection of essays addresses this deficit. The closely interconnecting individual chapters trace and, in part, revise the history of concepts of the subject and self in classical and post-classical texts. Whereas previous work in this area has concentrated almost exclusively on philosophical texts, this collection also examines other genres, especially poetry.